ON COMPOUND WORDS FROM A TYPE OF NAME IN TURKMEN TURKISH - Engin Gokçur (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2017)
Conjugation is the gathering of two or more words to create new concept. One of the most referenced way of lexicalising in Turkish is conjugation. In general, expressions consisted of indefinite noun phrase, adjective clauses and common finite verbs form compound word when they mean a new concept. In this study, compound words have been determined by researching literary works and dictionaries of Turkmen Turkish. A good part of compound words in Turkmen Turkish is consisted of Turkish originated words. Besides, some compounds words consisted of gathering of quoted words are also available. Especially Russian, French and Arabic words are much more in compound words of this group. Otherwise, other part of compound words is complex. In some part of words in this group first word becomes Turkish and second one may be a quoted word. Or first word is quoted and second one is Turkish. As a result of this examination in Turkmen Turkish, great majority of these compound words consist of two nominative words. Compound words in this form actually is an indefinite name that has improved. Also, there are some compound words formed of indefinite noun phrase and adjective clauses. Some of these words have consisted as a result of Arabic and Persian phrases. Likewise, it is possible to see some statements that take a fix structure and become compound words.